KEMUDAHAN INVESTOR DALAM PROSES INVESTASI MODAL ASING DI BANTEN - Rina Yulianti (Universitas Sultan Ageng Tirtayasa, 2015)
Investment is the investment made by local and international companies.And Banten is one area that many ogled for investment, so Banten had to do a lot ofpreparation to provide convenience services. With the increase in the area of investmentwill be realized if there is a potential area that can be